2021
DOI: 10.7150/jca.62281
|View full text |Cite
|
Sign up to set email alerts
|

uPAR: An Essential Factor for Tumor Development

Abstract: Tumorigenesis is closely related to the loss of control of many genes. Urokinase-type plasminogen activator receptor (uPAR), a glycolipid-anchored protein on the cell surface, is controlled by many factors in tumorigenesis and is expressed in many tumor tissues. In this review, we summarize the regulatory effects of the uPAR signaling pathway on processes and factors related to tumor progression, such as tumor cell proliferation, adhesion, metastasis, glycolysis, tumor microenvironment and angiogenesis. Overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 182 publications
0
11
0
4
Order By: Relevance
“…Based on these observations, it may be speculated that KLF4 may play a double role in the maintenance of the QCCs pool by maintaining a stemness state and restraining proliferation at the same time. In addition to KLF4, lung QCCs were characterized by an increased expression of urokinase plasminogen activator surface receptor (uPAR), a component of the plasminogen activation system involved in tumorigenesis, metastasis, EMT and chemoresistance [ 53 ], and by the two stemness-associated surface markers CD44 and CD166. Similarly, colorectal QCCs showed an increased expression of factors involved in stemness and self-renewal such as AXIN2, LGR5 and BMI1.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these observations, it may be speculated that KLF4 may play a double role in the maintenance of the QCCs pool by maintaining a stemness state and restraining proliferation at the same time. In addition to KLF4, lung QCCs were characterized by an increased expression of urokinase plasminogen activator surface receptor (uPAR), a component of the plasminogen activation system involved in tumorigenesis, metastasis, EMT and chemoresistance [ 53 ], and by the two stemness-associated surface markers CD44 and CD166. Similarly, colorectal QCCs showed an increased expression of factors involved in stemness and self-renewal such as AXIN2, LGR5 and BMI1.…”
Section: Discussionmentioning
confidence: 99%
“…Circ_0003340 has previously been shown to be dysregulated in ESCC and facilitated ESCC cell proliferation, migration and invasion, and arrested apoptosis 25 . Angiogenesis is an important basis for tumor cell proliferation and metastasis, and the development of antiangiogenic drugs has become a hot spot in cancer research 26 . Our study identified a high abundance of circ_0003340 in ESCC, and found that knockdown of circ_0003340 notably restrained ESCC cell proliferation, migration, invasion and tube formation, but enhanced apoptosis.…”
Section: Discussionmentioning
confidence: 53%
“… 25 Angiogenesis is an important basis for tumor cell proliferation and metastasis, and the development of antiangiogenic drugs has become a hot spot in cancer research. 26 Our study identified a high abundance of circ_0003340 in ESCC, and found that knockdown of circ_0003340 notably restrained ESCC cell proliferation, migration, invasion and tube formation, but enhanced apoptosis. Moreover, circ_0003340 silencing also curbed tumor growth in vivo.…”
Section: Discussionmentioning
confidence: 58%
“…uPAR is a highly glycosylated protein that is anchored on the cell membrane surface in the form of glycosylphosphatidylinositol (GPI). [19][20][21] uPAR/uPA is involved in the progression of glioma, including tumorigenesis, cell proliferation, cell migration, adhesion, tumor invasion, and other pathological processes. [22][23][24] Downregulation of uPAR expression by small…”
Section: Discussionmentioning
confidence: 99%